2015
DOI: 10.4103/2279-042x.155755
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in the elderly

Abstract: Objective:The objective was to assess the frequency of polypharmacy and potential complications among local seniors.Methods:A cross-sectional convenience sample of 59 adults aged above 65 years was interviewed at Cuyahoga county (U.S. state of Ohio) senior programs. Polypharmacy was defined as more than five prescribed medications. Primary outcomes were frequent missed doses, one or more duplicate drug/s, and equal or more than one contraindicated drug combinations.Findings:Among seniors with the mean age of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 10 publications
0
43
1
7
Order By: Relevance
“…It can increase the risk of drugs interaction, low adherence to medication, and adverse drug reactions. 7,8 Indonesian regulation obligates the prescription of generic drugs to ensure accessibility of medication to all population. In this study, the majority of prescribed drugs were generic drugs.…”
Section: Resultsmentioning
confidence: 99%
“…It can increase the risk of drugs interaction, low adherence to medication, and adverse drug reactions. 7,8 Indonesian regulation obligates the prescription of generic drugs to ensure accessibility of medication to all population. In this study, the majority of prescribed drugs were generic drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Bei ihnen bestehen mit höherer Wahrscheinlichkeit mehrere Begleiterkrankungen und eine erhebliche Polypharmazie [11]; daher ist es wahrscheinlich, dass eine Modifikation ihres häuslichen Medikationsschemas erforderlich ist, wenn sie wegen einer Hüftfraktur stationär aufgenommen werden. …”
Section: Der äLtere Frakturpatientunclassified
“…Hence, Golchin et al conducted a study on 59 patients aged 65+ and proved polypharmacy with 35.6% of the examinees. 11 Opposite to our opinion, results of a UK study that covered 1,900 patients aged 65+ indicated that the number of polypharmacy patients grew as the time passed. Thus, 15.1% of patients used 5 to 9 drugs in 2003, and the figures rose up to 25.2% in 2011.…”
Section: Discussionmentioning
confidence: 99%